Influence of nutritional support on tolerability and results of treatment in patients with newly diagnosed hemoblastoses received program chemotherapy - N. P. Shen’; A. S. Minin; E. Yu. Gaydym; T. I. Ksenzova (Онкогематология, 2022)
Background. Nutritional deficiency in malignant hematological diseases is a common condition that contributes to a decrease in functionality, tolerability of anticancer treatment and patient quality of life, and an increase in mortality rates. Often, malnutrition develops even before the start of anticancer treatment or during therapy and often remains unrecognized up to pronounced stages. despite the obvious importance of assessing and correcting the nutritional status in patients with hematological malignancies, this problem remains poorly understood.Aim. To evaluate the effect of nutritional support on the tolerability and results of treatment in patients with hemoblastoses.Materials and methods. The study included 40 patients with newly diagnosed hemoblastoses with nutritional deficiency or at risk of its development, who received program chemotherapy. patients were randomized into 2 comparable groups: in the main group (n = 20) patients received 2–3 bottles of Nutridrink compact protein mixture per day for 30 days, in the control group (n = 20) they ate at their own discretion without the use of additional enteral nutrition.Results. Comparative results of laboratory monitoring showed a significant increase in albumin levels in the main group compared with the control group (p <0.01). In the main group, less severe gastrointestinal toxicity of systemic anticancer therapy was observed: a tendency to a lower incidence of diarrhea and mucositis, a statistically significant reduction in the frequency of constipation, and a significant 2.8-fold decrease in the frequency of taste changes (25 % versus 70 %). Assessment of hematological toxicity showed that pancytopenia persisted in the control group (decrease in leukocytes, erythrocytes, hemoglobin, hematocrit and platelets levels), which was absent in the main group; leukocytes, hemoglobin, hematocrit, platelets and eosinophils were statistically significantly lower compared to the main group.Conclusion. The use of the Nutridrink compact protein mixture within 30 days from the start of treatment in patients with newly diagnosed hemablastoses contributed to an increase in albumin level, and reduced the incidence of gastrointestinal and hematological toxicity during systemic antitumor therapy.